International encyclopedia of economic sociology - Beckert, Jens, 1967-; Zafirovski, Milan, 1958- (Routledge, 2011)
The International Encyclopedia of Economic Sociology is the first encyclopedia in the field and a timely response to the surge of interest in economic sociology over the last 30 years. Economic Sociology deals with the multiple and complex relations between economy and society. In particular, it focuses on the impact of social, political and cultural factors on economic behaviour. The Encyclopedia gives comprehensive and accessible coverage of the wide range of areas and subjects covered by the field, including, amongst many others, such major topics as consumption, corrupti.